“Entrenched practices and other biases”: unpacking the historical, economic, professional, and social resistance to de-implementation - Montini, Theresa; Graham, Ian D (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background In their article on “Evidence-based de-implementation for contradicted, unproven, and aspiring healthcare practices,” Prasad and Ioannidis (IS 9:1, 2014) referred to extra-scientific “entrenched practices and other biases” that hinder evidence-based de-implementation. Discussion Using the case example of the de-implementation of radical mastectomy, we disaggregated “entrenched practices and other biases” and analyzed the historical, economic, professional, and social forces that presented resistance to de-implementation. We found that these extra-scientific factors operated to sustain a commitment to radical mastectomy, even after the evidence slated the procedure for de-implementation, because the factors holding radical mastectomy in place were beyond the control of individual clinicians. Summary We propose to expand de-implementation theory through the inclusion of extra-scientific factors. If the outcome to which we aim is appropriate and timely de-implementation, social scientific analysis will illuminate the context within which the healthcare practitioner practices and, in doing so, facilitate de-implementation by pointing to avenues that lead to systems change. The implications of our analysis lead us to contend that intervening in the broader context in which clinicians work—the social, political, and economic realms—rather than focusing on healthcare professionals’ behavior, may indeed be a fruitful approach to effect change.